Hidden heir, Italian wife - Collins, Dani (Harlequin presents, 2025)
"Since her night of pure, indulgent passion with Jackson Visconti, Brielle Hughes has been a devoted single mother. In Bree's world, men -- fathers -- cannot be relied on. Until three years later, the unforgettable Italian billionaire bursts back into her life ... demanding her hand in marriage!" --